Deep ocean microorganisms yield mechanistically-novel anticancer agents - Fenical, William (Henry Stewart Talks, 2013)
Structurally unprecedented marine bacterial metabolites, Developing new molecules for the treatment of cancer, Discovery of the protein targets of apoptosis-inducing metabolites, Developing the potential of natural products to treat cancer by alternative mechanisms of action, Discoveries of GRP94, myosin II and related cellular proteins as targets of new cytotoxins
Reviewed at 2021/09/23